TALKING SCIENCE: LANGUAGE, LEARNING, AND VALUES (Author: Jay L. Lemke) - Wolfe, Lila F. (McGill Journal of Education / Revue des sciences de l’éducation de McGill, 1992)
Jay L. Lemke. TALKING SCIENCE: LANGUAGE, LEARNING, AND VALUES. Norwood, NJ: Ablex Publishing Corp., 1990. 261 pp. 24.95.